Hb Agenogi [β 90(F6)Glu→Lys (G AG> A AG) HBB: C.271G>A)] in a Pregnant Thai Woman - Panyasai S. (2017)
© 2016 Taylor & Francis. Hb Agenogi [β90(F6)Glu→Lys (GAG > AAG) HBB: c.271G > A)] is a very rare β-globin chain variant. We report for the first time this hemoglobinopathy in a pregnant 20-year-old Thai woman. She was seen by an obstetrician at her 14th week of gestation. She was pale and had an inflammatory lesion of her lower left leg. The hemoglobin (Hb) analysis by high performance liquid chromatography (HPLC) and low pressure liquid chromatography (LPLC) showed a peak of abnormal Hb at the C window. On capillary electrophoresis (CE), the abnormal Hb peak was observed at electrophoretic zone 4 that corresponded to the Hb E (HBB: c.79G > A) peak. Direct DNA sequencing revealed a GAG > AAG mutation at codon 90 of the β-globin gene. Thus, even though Hb Agenogi is very rare, it can be found in Thai people. The knowledge and understanding of this hemoglobinopathy will be used to assist in diagnosis, management and counseling for patients.